Isolation and characterization of lantana camara seeds extract for their therapeutic potential - SURINDER SINGH; NARESH SINGH GILL (International Journal of Pharma and Bio Sciences, 2018)
The objective of this study is to isolate and study the characterize of Lantana camara methanol seed extract for their therapeutic potential. Lantana camara Linn., is a flowering ornamental plant that belongs to family Verbenaceae. It is also known as Lantana, Wild Sage, Surinam Tea Plant, Spanish flag and West Indian lantana. Phytochemical studies have resulted in the isolation of various terpenoids, steroids and flavonoids. It is an excellent source of various classes of bioactive natural products like steroids, oliogosaccharides, triterpenoids, glycosides and naphthoquinones. The plant shows antioxidant, antimicrobial, antifungal, antiviral, antiulcerogenic, mosquito larvicidal, wound healing, anti-helmintic, insecticidal, nimaticidal, antipyretic, anti-hyperglycemic immunosupressant and antitumor activity. Hence, the present study was done to isolate and characterise the Lantana camara seeds for its therapeutic potential. For the study purpose, first Lantana camara seeds were collected, cleaned, washed and dried in shade. Seeds were powdered and weighed 100 g. Powdered seeds were subjected to cold maceration with solvent for 72 hours. Extract was filtered and partially concentrated. Defatting of concentrate was carried out 3 times by hexane in separating funnel. The methanol fraction was separated and concentrated on water bath. The crude extract thus obtained was weighed. Then the obtained extract was used for its pre-liminary phytochemical study. The phytochemical screening of the methanolic extract was carried out for various constituents present in it such as: carbohydrates, fixed oils, terpenoids, alkaloids, saponins, tannins, flavanoids, steroids, volatile oils, anthraquinone glycosides, coumarin glycosides, proteins by following standard procedure. The 50% methanol seed extract was screened for phytochemicals and subjected to qualitative and quantitative test for antioxidant activity with 1,1-diphenyl-2-picrylhydrazyl free radical and Hydrogen peroxide scavenging activity. The extract was subjected to various isolation techniques like Thin Layer Chromatography, Column chromatography and characterization of compound with Infra Red and Nuclear Magnetic Resonance. The extract was found to produce a antioxidant activity in a dose dependent manner with both methods. Isolated and characterized compound was triterpenoid derivative. The seed extract has potential source of antioxidant component which was isolated and characterized.